Early-stage bifurcation of crystallization in a sphere - Mbah, Chrameh Fru; Wang, Junwei; Englisch, Silvan; Bommineni, Praveen Kumar; Varela Rosales, Nydia; Spiecker, Erdmann; Vogel, Nicolas; Engel, Michael (Nature Communications, 2023)
Bifurcations in kinetic pathways decide the evolution of a system. An example is crystallization, in which the thermodynamically stable polymorph may not form due to kinetic hindrance. Here, we use confined self-assembly to investigate the interplay of thermodynamics and kinetics in the crystallization pathways of finite clusters. We report the observation of decahedral clusters from colloidal particles in emulsion droplets and show that these decahedral clusters can be thermodynamically stable, just like icosahedral clusters. Our hard sphere simulations reveal how the development of the early nucleus shape passes through a bifurcation that decides the cluster symmetry. A geometric argument explains why decahedral clusters are kinetically hindered and why icosahedral clusters can be dominant even if they are not in the thermodynamic ground state.
CRIS-Team Scopus Importer:2023-09-08